Wound closure techniques and postoperative wound management in aesthetic surgery: an evidence-based narrative review - Gómez, América C. (International Surgery Journal, 2026)
Optimal wound closure and postoperative wound management are critical determinants of outcomes in aesthetic surgery, where success is defined not only by complication avoidance but also by scar quality and patient satisfaction. This narrative review synthesizes current evidence on layered closure strategies, suture materials and techniques, tension-reducing methods such as progressive tension sutures, and postoperative topical wound and scar management. Particular attention is given to topical agents commonly used in Latin American clinical practice, including acexamic-acid–based formulations (Recoveron®/Recoveron N®) and pirfenidone-based topical therapy (commercially aligned with Kitoscell-Q®).